Not all viruses in nature are human enemies: a perspective on aquatic virus ecology in Brazil - Junger,Pedro Ciarlini (2020)
Abstract: Viruses cause various diseases in humans through vector-borne (e.g., Zika and dengue fever), airborne (e.g., measles) and water-borne (e.g., hepatitis) transmission, as well as direct physical contact (e.g., AIDS and herpes). Recently, the new coronavirus (SARS-CoV-2) pandemic has triggered the greatest global health crisis in a century. However, not all viruses in nature are human enemies. A vast body of literature indicates that viral infection is vital for ecosystem functioning by affecting nutrient cycling, controlling species growth and enhancing biodiversity. Here we provide a perspective on the ecological role of viruses in nature, with special focus on Brazilian aquatic ecosystems.